Implementasi Asesmen dalam Melihat Kebutuhan Anak Berkebutuhan Kusus Di TK LB C1 Dharma Rena Ring Putra I Yogyakarta - Muhamad Abdul Rosid (UMSU, 2018)
AbstractIn the context of education for students with disability, Assessment is functioned to measure the capability and difficulty of students in learning as a tool to determine what the students need in their learning process. In other words, assessment is used to know and determine where the problems of students faced and what the necessities of students to support their learning process. This research has purposed to express the Implementation of Assessment of special education (SLB) Teacher and The Cooperation of Teacher with Outsiders. The result of this research showed that there are two aspects of the implementation of teacher’s assessment. The first aspect is from their limitations, and the second aspect is from the ability to understand the material in the class. Therefore, the effort in improving the capability of students is very needed the cooperation with outsiders, such as the specialist teacher, student guardian or parents.